PEMBERDAYAAN PEREMPUAN DALAM PERSPEKTIF ISLAM: KAJIAN HUKUM, SOSIAL, DAN GENDER DI DUNIA MODERN - Harahap, Fitri Habibah; Dalimunthe, Rizki Hamonangan; Siregar, Fatimah (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study analyzes the empowerment of women from an Islamic perspective through a literature review, focusing on the legal, social, and gender aspects in the modern world. The findings indicate that Islamic law provides protection for women's rights, including inheritance and education rights. The social aspect emphasizes the importance of women's roles in society, while the gender analysis affirms the equality between men and women. Despite challenges in implementation, this study concludes that women's empowerment based on Islamic teachings can contribute to more just and sustainable social change.